Lumbosacral region herpes zoster case in healthy child - Mahmut Demir; Mustafa Aksoy (Van Tıp Dergisi, 2017)
Herpes zoster is an acute dermatomal viral infection characterized by clinically painful and erythematous vesicular rash in the area of the associated dermatome as a result of varicella zoster virus reactivation, which is quite rare in childhood and mostly seen in immunocompromised and elderly patients. HZ is clinically better in childhood and rarely accompanies pain and postherpathic neuralgia in lesions holding more of the thoracic dermatomic areas. Herpes zoster cases seen in childhood usually have an underlying predisposing factor such as a trigger stress factor or immunodeficiency. İn this case, were porta 4 years old healthy boy diagnosed as zona zoster patients with prior history of surgery.